Comparison of Clean and Healthy Living Behavior Before and After Handwashing Promotion at Tahfidz One Qur'an Islamic Boarding School Jambi - Hakim, Khaila Nur; Budiarso, Linda S. (Jambura Medical and Health Science Journal, 2025)
Introduction: Clean and healthy living behavior (Perilaku Hidup Bersih dan Sehat, PHBS) is essential in improving public health, particularly through handwashing with soap (Cuci Tangan Pakai Sabun, CTPS), which has been proven to prevent infectious diseases effectively. However, this practice remains low in pesantren (Islamic boarding schools) due to limited knowledge and the absence of established habits. This study aims to compare the knowledge and attitudes of santri (students) towards CTPS before and after a health promotion program at Tahfidz One Qur'an Islamic Boarding School Jambi.Method: This study applied a quasi-experimental one-group pretest-posttest design involving 64 students selected through convenience sampling. Data were collected using pretest and posttest questionnaires and analyzed with the Wilcoxon signed-rank test.Results: The results showed a significant improvement in knowledge (P=0.000), with an average increase of 3.64, and in attitudes (P=0.000), with an average increase of 6.02.Conclusion: The health promotion program effectively enhanced the understanding and shaped positive attitudes of the santri towards the practice of CTPS. Keywords: Clean and healthy living behavior, handwashing with soap, health promotion